Pengembangan Inovasi Digital Marketing untuk Meningkatkan Kualitas Pelayanan di PT Sasana Lintas Indo - Juleha Safitri; Indra Saputra; Indra Saemona; Yetti Afrida Indra (EMPOWERMENT: Journal of Community Practice, 2025)
This community service aims to develop digital marketing innovations in order to improve service quality at PT Sasana Lintas Indo. The digital era has fundamentally changed business paradigms, requiring companies to adapt to the latest technology trends. Through a participatory action research approach, this activity involves a series of workshops, training, and mentoring for employees of PT Sasana Lintas Indo in optimizing their digital marketing strategies. The results of the service indicate a significant improvement in the company's service quality through the implementation of customer relationship management (CRM), the use of social media as a communication channel, the development of relevant content marketing, and comprehensive customer data analysis. This activity contributed to a 27% increase in customer satisfaction, faster service response times with the average response time decreasing from 24 hours to 2 hours, and a 45% increase in engagement rate on the company's digital platforms. This service concludes that the proper implementation of digital marketing can be a catalyst for transforming the company's service quality in the digital era.